2010
DOI: 10.1371/journal.pone.0011658
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Activatable Fibrinolysis Inhibitor (TAFI) Deficient Mice Are Susceptible to Intracerebral Thrombosis and Ischemic Stroke

Abstract: BackgroundThrombus formation is a key step in the pathophysiology of acute ischemic stroke and results from the activation of the coagulation cascade. Thrombin plays a central role in this coagulation system and contributes to thrombus stability via activation of thrombin-activatable fibrinolysis inhibitor (TAFIa). TAFIa counteracts endogenous fibrinolysis at different stages and elevated TAFI levels are a risk factor for thrombotic events including ischemic stroke. Although substantial in vitro data on the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…13 Notwithstanding promising results, not all studies proclaim that inhibition of 1 antifibrinolytic constituent is sufficient to overcome thrombosis. 31,37,38 Because TAFI and PAI-1 have complementary roles that are localized at the fibrin surface, we hypothesized that simultaneous targeting of the 2 antifibrinolytics would amplify the profibrinolytic capacity in a fibrin-localized manner. Fibrinolysis is driven by enzymatic activation of plasminogen into active plasmin through …”
Section: Discussionmentioning
confidence: 99%
“…13 Notwithstanding promising results, not all studies proclaim that inhibition of 1 antifibrinolytic constituent is sufficient to overcome thrombosis. 31,37,38 Because TAFI and PAI-1 have complementary roles that are localized at the fibrin surface, we hypothesized that simultaneous targeting of the 2 antifibrinolytics would amplify the profibrinolytic capacity in a fibrin-localized manner. Fibrinolysis is driven by enzymatic activation of plasminogen into active plasmin through …”
Section: Discussionmentioning
confidence: 99%
“…1 We here show that inhibition of PAI-1 and TAFI can protect mice from ischemia/ reperfusion injury by reducing cerebral fibrin(ogen) deposition and improving cerebral reperfusion. Remarkably, using the same model, Kraft et al 12 found that TAFI-deficient mice were unprotected. A plausible explanation could be the fact that MA-TCK26D6 specifically impairs the antifibrinolytic capacity of TAFI while preserving the anti-inflammatory potency of TAFI.…”
Section: September 2016mentioning
confidence: 92%
“…Immunoreactivity for fibrin(ogen) (anti-Fibrinogen pAb 1:500; Acris Antibodies) 24 and occludin (antioccludin pAB 1:1000; Abcam) in the ischemic cortices and basal ganglia was detected and quantified by Western blot.…”
Section: Western Blotmentioning
confidence: 99%